Sliding discharge optical emission characteristics - Lago, V. (2009)
In this work, several optical studies in an atmospheric pressure sliding plasma sheet have been performed. This discharge is generated using two electrodes flush mounted on an insulating flat plate (upper electrodes), and a third electrode flush placed on the opposite side of the plate facing the upper inter electrode gap (lower electrode). A dc negative voltage is applied to one of the two upper electrodes and to the lower electrode, while the other upper electrode is biased with an ac voltage. In this configuration a sliding discharge is produced on the flat plate within the upper electrode's gap. The sliding discharge optical emission of the spectral bands corresponding to the 0-0 transition of the second positive system of N2 (λ = 337.1 nm) and the first negative system of N2 + (λ = 391.4 nm) have been measured. Also the light spatial distribution in the plasma sheet has been studied using a CCD camera coupled to interferential filters corresponding to the wavelengths investigated. The reduced electric field in the plasma sheet has been derived from the measurement of the intensity ratio of the Nitrogen lines. This study has been realized varying the amplitude of the dc voltage and the amplitude and frequency of the ac voltage. The reduced electric field strength is found to be almost constant for all the experimental conditions, with a value of 500 ± 100 Td (1 Td = 1.10-17 V cm2). © 2006 IEEE.